1999
DOI: 10.1139/o99-038
|View full text |Cite
|
Sign up to set email alerts
|

Function and assembly of nuclear pore complex proteins

Abstract: Nuclear pore complexes (NPCs) are extremely elaborate structures that mediate the bidirectional movement of macromolecules between the nucleus and cytoplasm. The current view of NPC organization features a massive symmetrical framework that is embedded in the double membranes of the nuclear envelope. It embraces a central channel of as yet ill-defined structure but which may accommodate particles with diameters up to 26 nm provided that they bear specific import/export signals. Attached to both faces of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 75 publications
0
10
0
1
Order By: Relevance
“…However, they also differ: a substantial fraction of ELYS has a strong intranuclear presence. It has been shown that certain Nups, such as Nup98, Rae 1, and Nup50, shuttle into the nucleus and reside there part time (13,(20)(21)(22)(23)(24). ELYS may resemble these Nups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also differ: a substantial fraction of ELYS has a strong intranuclear presence. It has been shown that certain Nups, such as Nup98, Rae 1, and Nup50, shuttle into the nucleus and reside there part time (13,(20)(21)(22)(23)(24). ELYS may resemble these Nups.…”
Section: Discussionmentioning
confidence: 99%
“…Nup62, a component of the nuclear pore central channel domain, is recruited relatively late in the nuclear envelope reassembly process, i.e., during telophase (19,20), whereas the Nup107-160 complex is recruited early (5). Immunofluorescence on HeLa cells revealed that ELYS begins to associate with the chromatin͞ nuclear periphery in late anaphase, well before Nup62 (Fig.…”
Section: Elys Is Recruited Early In the Nuclear Envelope Reassembly Pmentioning
confidence: 97%
“…6C). Furthermore, the diffuse pattern exclusive of the region for the chromosome represented co-localization with nucleoporin p62, a component of the nuclear pore complex (31) (Fig. 6D).…”
Section: Coiled-coil Formation Within the Central Stalk Domain Of Krmmentioning
confidence: 98%
“…Early assembly intermediates clearly have a pore membrane domain but apparently very little else and are presumably stabilized by integral pore membrane proteins such as Pom121p, which is recruited early in the reassembly process (10,11). Gp210, a pore membrane protein known to be a major constituent of the lumenal ring, is apparently recruited later in NPC assembly (11). Gp210 is also hyperphosphorylated at the early stages of mitosis, and this modification may be important to initiate the mitotic disassembly of the NPC and nuclear envelope (12).…”
Section: The Pore Membrane Domain and Formationmentioning
confidence: 99%